Smartphone applications validated for joint angle measurement: a systematic review. Issue 1 (March 2019) - Longoni, Luca; Brunati, Roberto; Sale, Patrizio; Casale, Roberto; Ronconi, Gianpaolo; Ferriero, Giorgio
Abstract : Mobile health apps are growing constantly in number and popularity. Some mobile apps are used for clinical assessment, and consequently need to be verified and validated appropriately, along with the mobile platform, to ensure their safe and effective operation. We review the current literature on available smartphone goniometric apps validated for joint angle measurement and their main psychometric characteristics. A literature search of Medline and Scopus databases was performed to select papers on smartphone commercial apps validated for joint angle measurement and relevant to Physical Medicine and Rehabilitation. A platform search verified whether the selected apps were still available for download. The literature search identified 126 papers in Medline and 113 in Scopus, 49 of which were selected. They dealt with the validation of 23 apps, eight of which were no longer available and therefore excluded from the review. Psychometric characteristics of the selected apps were robust, but heterogeneity of the studies did not enable comparisons between apps to identify the most valid one. The increase in the number of apps and validation studies highlights the growing interest in this new approach for measuring body angles. Given the precarious commercial availability of some apps, when research is the goal, it is advisable to select apps with the longest durability. A need continues to exist for validation studies on available apps focused on goniometric measurement in gait or during performance of therapeutic exercises in neurological and orthopedic disorders.